Social interaction and geographic diffusion of iron-biofortified beans in Rwanda - Funes, Jose; Sun, Laixiang; Sedano, Fernando; Baiocchi, Giovanni; Benson, Todd (Wiley, 2022)
This study analyzes smallholder farmers’ decisions to adopt beans with higher levels of dietary iron developed through a conventional breeding technique called biofortification. We approach this study by applying spatial econometric techniques to estimate neighborhood influence and to determine the factors driving the adoption of iron-biofortified beans (IBB). We employ a cross-sectional, nationally representative survey of bean producing households from 2015 bean growing season B in Rwanda, and present results for growers of both bush and climbing varieties of beans. The results show geographic diffusion of iron bean planting material occurs among neighboring farmers that exhibit interdependent decision-making patterns, as well as similar characteristics relative to the group. Some policy implications can be drawn from the results. First, a differentiated geographical targeting strategy for bush and climbing bean varieties as a function of farmer and farm characteristics should increase iron bean adoption rates. Second, strengthening partnerships with delivery agents and extensionists should stimulate the adoption of IBB varieties. And finally, technology-promotion programs that consider progressive farmers and strengthen social interactions and group activities among peer networks should increase the spread of information and diffusion of IBB.